2017
DOI: 10.1016/j.jped.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imbalances in syndromic congenital heart disease

Abstract: These data showed that patients presenting CHD with extra cardiac anomalies and exclusion of 22q11.2 DS should be investigated by CMA. The present study emphasizes the possible role of CNVs in CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…Eugen-Matthias Strehle et al [ 55 ] studied 20 patients with 4q deletions and found significant genotype-phenotype correlations at a single gene level, linking specific phenotypes to individual genes. The authors reported an imbalance slightly smaller than ours and proposed a potentially critical region for 4q35 associated to CHD compromising the SORBS2 gene (616349) [ 56 ]. In addition, the patient from our cohort disclosed also a duplication on the CES region.…”
Section: Discussionmentioning
confidence: 84%
“…Eugen-Matthias Strehle et al [ 55 ] studied 20 patients with 4q deletions and found significant genotype-phenotype correlations at a single gene level, linking specific phenotypes to individual genes. The authors reported an imbalance slightly smaller than ours and proposed a potentially critical region for 4q35 associated to CHD compromising the SORBS2 gene (616349) [ 56 ]. In addition, the patient from our cohort disclosed also a duplication on the CES region.…”
Section: Discussionmentioning
confidence: 84%
“…Due to the large sample size and completeness of our regional CHD registry, we were able to stratify the probability of genetic diagnoses according to the specific heart defect, using not only results from karyotyping and FISH for 22q11.2, but CMA, genetic testing for specific syndromes and exome sequencing in selected cases as well. Although several recent cohorts have studied aneuploidy or 22q11.2 deletion syndrome in CHD cases, 22,23,26,29 evidence on the prevalence of other structural chromosome abnormalities and sequence variants for specific heart defects is limited. IAoA, PA-VSD and AVSD were most associated with the presence of genetic diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital heart disease (CHD) is a common malformation affecting approximately six per 1000 live births, occurring as an isolated trait or related to multiple congenital anomalies [ 1 ]. Despite anatomical evaluation has a great contribution to the diagnosis and treatments of CHD, the hemodynamic evaluation is also indispensable.…”
Section: Introductionmentioning
confidence: 99%